2018
DOI: 10.1029/2018jb015642
|View full text |Cite
|
Sign up to set email alerts
|

Recurring Slow Slip Events and Earthquake Nucleation in the Source Region of the M 7 Ibaraki‐Oki Earthquakes Revealed by Earthquake Swarm and Foreshock Activity

Abstract: Slow slip events (SSEs) on the plate interface are closely related to the occurrence of earthquakes and often trigger earthquake swarms in subduction zones. Moreover, some SSEs, accompanied by intensive foreshocks, precede large interplate earthquakes. Therefore, detecting and monitoring SSEs is important for assessing the potential of future large earthquakes. However, there are many SSEs not followed by large earthquakes, and it is unclear whether these can be distinguished from SSEs preceding large earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 67 publications
9
48
1
Order By: Relevance
“…Such coexistence of ordinary earthquakes and tremors at similar depth have not been observed in the Nankai subduction zone but observed in the Japan Trench. Some clusters of shallow tremor (Ito et al, ) and VLFEs (Y. Asano et al, ; Matsuzawa et al, ) have been reported along the Japan Trench, as well as earthquake swarms (Nishikawa & Ide, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Such coexistence of ordinary earthquakes and tremors at similar depth have not been observed in the Nankai subduction zone but observed in the Japan Trench. Some clusters of shallow tremor (Ito et al, ) and VLFEs (Y. Asano et al, ; Matsuzawa et al, ) have been reported along the Japan Trench, as well as earthquake swarms (Nishikawa & Ide, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Japan Trench, VLFs have been detected using onshore broadband seismometers (7), and SSEs and tectonic tremors preceding the Tohoku-Oki earthquake have been inferred from oceanbottom pressure gauge and seismograph observations (2,3). Other indicators of aseismic slip are from observations of repetitive ruptures on the same fault patches, called repeating earthquakes ("repeaters") (8), and increases in the seismicity rate without a distinguishable mainshock, called earthquake swarms (9). Previous studies (8)(9)(10) have reported recurrent SSEs in the Japan Trench based on analyses of repeating earthquakes and earthquake swarms.…”
mentioning
confidence: 99%
“…Most of their epicenters were located in the slightly downdip side of the network. While the tremor region largely coincides with the VLFE region (Matsuzawa et al, ), it appears almost complementary to the regions of repeating earthquakes (Uchida & Matsuzawa, ) and regular earthquake swarms (Nishikawa & Ide, ), and it lies between the coseismic and afterslip regions (Figure ). Figure shows examples of tremor seismograms recorded by the broadband OBSs where we can clearly see tremor signals in the high‐frequency band (2–8 Hz) as well as possible VLFE signals in the low‐frequency band (0.02–0.05 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Geophysical Research Letters repeating earthquakes (Uchida & Matsuzawa, 2013) and regular earthquake swarms (Nishikawa & Ide, 2018), and it lies between the coseismic and afterslip regions (Figure 1). Figure 2 shows examples of tremor seismograms recorded by the broadband OBSs where we can clearly see tremor signals in the high-frequency band (2-8 Hz) as well as possible VLFE signals in the low-frequency band (0.02-0.05 Hz).…”
Section: 1029/2019gl082468mentioning
confidence: 99%
See 1 more Smart Citation